Pengembangan Media Pembelajaran HAM berbasis Video Animasi bagi Generasi Muda Di Era Digital Di MGMP PPKn SMA Kota Surakarta - Triyanto; noventari, Widya Noventari; Yudi Ariana (Jurnal Pengabdian UntukMu NegeRI, 2025)
Awareness of the importance of Human Rights (HAM) in community life must continue to be enhanced, considering that many cases of human rights violations occur in society, including within schools. Formal education plays a key role in increasing respect for and protecting human rights values. For this purpose, engaging learning media are needed for students. Learning media that align with the substance of human rights can take the form of animated videos. However, many teachers face difficulties in developing human rights education media based on animated videos. This activity aims to: 1) improve the knowledge, mastery, and understanding of civics teachers regarding human rights education materials and the development of learning media based on animated videos; 2) strengthen the capacity of civics teachers in developing human rights education learning media based on animated videos. The community service team carried out these activities through workshops and mentoring sessions. The implementation of the community service activities proceeded smoothly according to plan and received a positive response from the participants.